Respuesta :

Answer:

[tex]g(4a) = \frac{2}{4a + 3}[/tex]

Step-by-step explanation:

Given the function is [tex]g(t) = \frac{2}{t + 3}[/tex] ........... (1)

Now, we are given that [tex]g() = \frac{2}{4a + 3}[/tex] .......... (2)

Now, the left hand side of both the above equations (1) and (2) are similar and the only change is that t is replaced by 4a.

Therefore, the equation (2) can be written as  

[tex]g(4a) = \frac{2}{4a + 3}[/tex] (Answer)

Since we know that if [tex]g(t) = \frac{2}{t + 3}[/tex] then [tex]g(k) = \frac{2}{k + 3}[/tex], where k is any real value.

The value will be 4a.

Expression

In mathematics, an expression is defined as a set of numbers and mathematical operations that is formed according to rules which is dependent on the context.  

Given to us,

equation 1,

[tex]g(t) = \dfrac{2}{(t + 3)}[/tex]

equation 2,

[tex]g(\ \ ) = \dfrac{2}{(4a + 3)}[/tex]

Let's assume t=4a,

substituting the value of t in equation1, we get

[tex]g(t) = \dfrac{2}{(t + 3)}[/tex]

[tex]g(4a) = \dfrac{2}{(4a + 3)}[/tex]

As we can see we get equation 2 again, therefore, the value will be 4a.

Learn more about the expression:

https://brainly.com/question/13947055